Type designations for Neotropical water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae) - Perkins, Philip D. (Zootaxa, 2019)
Lectotypes are designated for the following species of Neotropical Hydrochus Leach, 1817: H. argutus Knisch, H. corruscans Bruch, H. drakei Knisch, H. ducalis Knisch, H. metallipes Knisch, H. pumilio Knisch, H. purpureus Knisch, H. secretus Knisch, and H. variabilis Knisch. A neotype is designated for H. tarsalis Chevrolat. Hydrochus metallipes is a new junior synonym of H. tarsalis. Hydrochus corruscans new status is removed from synonymy with H. obscurus Sharp. High resolution digital images of the habitus and male genitalia are given, as are photographs of the pin labels of all designated types.